An Overview of the Utilization of Common Waste as an Alternative Fuel in the Cement Industry - Tee How Tan; Kim Hung Mo; Jiayi Lin; Chiu Chuen Onn (Advances in Civil Engineering)
As concrete is one of the most commonly used construction materials, there is a massive production of cement, which causes cement manufacturing to be an energy-intensive industry. A significant amount of the cost of cement production, ranging from 20% to 25%, is attributed to thermal energy. In addition, the action of mining and burning fossil fuels results in the unfavorable emission of hazardous compounds into the environment. Therefore, the switch from conventional fossil fuels to alternative fuels (AFs) in the cement manufacturing business has attracted attention due to environmental and financial concerns. In this paper, four commonly used AFs are discussed, which are waste tires, municipal solid waste, meat and bone meal, and sewage sludge. It is found that each AF has a unique calorific value and properties, attributed to its source, treatment, and technology. Furthermore, the availability of AF is important as the amount varies depending on the location. In addition, their effects on gaseous emissions from the cement plant and the quality of clinker are found to be inconsistent. Thus, there will not be a single best type of AF option to be used in the cement industry. A good AF should be able to provide sufficient thermal energy while reducing the environmental impacts and costs. A careful analysis and multicriteria decision-making approach are always vital when employing AFs in order to prevent environmental problems, cost increases, as well as clinker quality degradation.